Rapid HPLC Quantification Approach for Detection of Active Constituents in Modern Combinatorial Formula, San-Huang-Xie-Xin-Tang (SHXXT) - Wu, Tung-Ying; Chang, Fang-Rong; Liou, Jing-Ru; Lo, I-Wen; Chung, Tang-Chia; Lee, Li-Yao; Chi, Chun-Chen; Du, Ying-Chi; Wong, Man-Hon; Juo, Suh-Hang Hank; Lee, Chun-Chen; Wu, Yang-Chang (Frontiers in Pharmacology, 2016)
San-Huang-Xie-Xin-Tang (SHXXT), one of the most important traditional Chinese medicinal formulas, is comprised by three herbal medicines, the rhizome of Rheum officinale [or R. tanguticum (Polygonaceae) (Dahuang in Chinese)], the root of Scutellaria baicalensis (Labiatae) (Huangqin in Chinese), and the rhizome of Coptis chinensis (Ranunculaceae) (Huanglian in Chinese) in the ratios of 2:1:1 or 1:1:1. This study is aimed to quantitate and qualify of SHXXT, by a rapid, convenient, and effective HPLC-PDA approach associated with LC-MS technique. Of which method, nine chosen major bioactive components in SHXXT, including aloe-emodin (Ale), baicalin (Ba), berberine (Be), coptisine (Co), palmatine (Pa), resveratroloside (Res), rhein (Rh), sennoside A (Se-A), and wogonin (Wo), were evaluated within 30 minutes. The nine chemical markers were monitored in a high sensitivity with a low detection limit of 0.01‒0.55 μg/mL and the correlation coefficient of the regression curve revealed a good linearity with R2 > 0.99. Moreover, the extraction solution system and the HPLC elution conditions were also optimized in the present study. This present developed protocol was then successfully applied to quantify nine chemical markers of ten SHXXT products from eight Taiwanese TCM pharmaceutical companies. In quantitative results, Res was found as the major compound in SHXXT-1~5 & 8 with significantly higher amounts than those in other products, indicating the products SHXXT-1~5 & 8 may use R. tanguticum as the raw material, which possessed a higher concentration of the bioactive composition Res, instead of R. officinale. Simultaneously, Ale, Rh, and Wo were less than 2% in these ten products. Different chemical profiles of commercial products indicated that, probably, each product with the same named formula might be regarded as a sole medicine and need to be investigated individually. Importantly, it is never too much to emphasize the importance of quality control in TCM development.